2000
DOI: 10.1211/0022357001773698
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate and Kynurenate in the Rat Central Nervous System Following Treatments with Tail Ischaemia or Diclofenac

Abstract: Kynurenate is an endogenous antagonist at the allosteric glycine site on the N-methyl-Daspartate (NMDA) receptor, and may have a role in ameliorating nociceptive processes through modulation of NMDA receptor function. While antinociceptive effects of nonsteroidal anti-in¯ammatory drugs (NSAIDs) are mediated peripherally and possibly centrally through inhibition of prostaglandin synthesis, there is also evidence for centrally mediated prostaglandin-independent antinociceptive effects that may result from increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 37 publications
(45 reference statements)
0
5
0
1
Order By: Relevance
“…Patients receiving low-dose aspirin, which preferentially inhibits COX-1, were significantly more likely to respond to treatment than placebo-treated subjects, suggesting that aspirin may be an efficacious adjunctive treatment for bipolar depression 176 . Interestingly, the COX-1 inhibitors, indometacin and diclofenac increased brain levels of KynA in the rat 177, 178 and KynA levels in both the plasma and the hippocampus were shown to be significantly increased one hour after a single dose of ibuprofen 179 . Whether the impact of COX inhibition on KynA is independent of its general anti-inflammatory effects remains to be determined but either way these data raise the possibility that changes in KP metabolism may contribute to the putative anti-depressant effects of COX inhibitors.…”
Section: Therapeutic Implicationsmentioning
confidence: 95%
“…Patients receiving low-dose aspirin, which preferentially inhibits COX-1, were significantly more likely to respond to treatment than placebo-treated subjects, suggesting that aspirin may be an efficacious adjunctive treatment for bipolar depression 176 . Interestingly, the COX-1 inhibitors, indometacin and diclofenac increased brain levels of KynA in the rat 177, 178 and KynA levels in both the plasma and the hippocampus were shown to be significantly increased one hour after a single dose of ibuprofen 179 . Whether the impact of COX inhibition on KynA is independent of its general anti-inflammatory effects remains to be determined but either way these data raise the possibility that changes in KP metabolism may contribute to the putative anti-depressant effects of COX inhibitors.…”
Section: Therapeutic Implicationsmentioning
confidence: 95%
“…Furthermore, it was proposed that increased brain formation of kynurenic acid (1,4‐dihydro‐4‐oxo‐quinoline‐2‐carboxylic acid (KYNA)) induced by NSAIDs, contributes to their analgesic efficacy probably through an inhibitory action on COX‐1 21. In fact, an increased formation of brain kynurenic acid (KYNA) has been suggested to contribute to the analgesic action of diclofenac, a relatively non‐selective COX‐inhibitor 22. KYNA is a metabolite of tryptophan and is synthesized in brain astrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is also evidence that diclofenac exhibits additional prostaglandin-independent properties that mediate its antinociceptive effects. For instance, diclofenac is able to inhibit H + -gated channels in sensory neurons, increase the concentration of kynurenate (an endogenous antagonist of NMDA receptors), stimulate the nitric oxide-cGMP-K + channels pathway, and activate metformin- and phenformin-dependent mechanisms to induce antinociception [1923]. On the other hand, several studies demonstrated antinociceptive and antihyperalgesic effects with the mixture of thiamine, pyridoxine, and cyanocobalamin in the models of hyperalgesia induced by carrageenan, in the pressure testing of the tail, and in the formalin model [24, 25].…”
Section: Discussionmentioning
confidence: 99%